Clinical appraisal of tafluprost in the reduction of elevated intraocular pressure (IOP) in open-angle glaucoma and ocular hypertension - Makoto Aihara (Dove Medical Press, 2010)
Makoto AiharaDepartment of Ophthalmology, University of Tokyo School of Medicine, Tokyo, JapanAbstract: An elevated intraocular pressure (IOP) is one of the most important risk factors for the development of glaucoma, which causes progressive optic neuropathy. Lowering IOP is currently the only therapeutic approach to the treatment of glaucoma. Tafluprost, a novel prostaglandin analogue, was recently launched onto the market as an ocular hypotensive agent. Tafluprost is potent in its affinity for the prostanoid FP receptor and in its intraocular lowering efficacy. Moreover, it enhances the ocular hemodynamics and has neuroprotective effects. Clinical studies have demonstrated its efficacy at decreasing intraocular pressure in patients with open-angle glaucoma or ocular hypertension.Keywords: open-angle glaucoma, normal tension glaucoma, receptor affinity, intraocular pressure